2020
DOI: 10.1016/j.bpj.2020.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Amoeboid Swimming Is Propelled by Molecular Paddling in Lymphocytes

Abstract: Mammalian cells developed two main migration modes. The slow mesenchymatous mode, like crawling of fibroblasts, relies on maturation of adhesion complexes and actin fibre traction, while the fast amoeboid mode, observed exclusively for leukocytes and cancer cells, is characterized by weak adhesion, highly dynamic cell shapes, and ubiquitous motility on 2D and in 3D solid matrix. In both cases, interactions with the substrate by adhesion or friction are widely accepted as a prerequisite for mammalian cell motil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 72 publications
9
59
0
Order By: Relevance
“…If any of the above‐mentioned tissues suffers from infection, swimming leukocytes are required to clear out the pathogen, since a single bacterium remaining in the bulk could act as a reservoir leading to chronic infection. Leukocytes will therefore need to quit adhesion and swim in order to reach it, a behaviour already described for effector T lymphocytes [Aoun et al., 2020]. In line with this, we provide here evidence that neutrophils can migrate on adherent substrates by alternating between high and low adhesion levels.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…If any of the above‐mentioned tissues suffers from infection, swimming leukocytes are required to clear out the pathogen, since a single bacterium remaining in the bulk could act as a reservoir leading to chronic infection. Leukocytes will therefore need to quit adhesion and swim in order to reach it, a behaviour already described for effector T lymphocytes [Aoun et al., 2020]. In line with this, we provide here evidence that neutrophils can migrate on adherent substrates by alternating between high and low adhesion levels.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, as of today, swimming of human neutrophils has not been reproduced. Nonetheless, we recently reported that human Effector T lymphocytes also swim [Aoun et al., 2020]. Supported by our experimental observations, we proposed a theoretical model for swimming migration based on a ‘molecular paddling’, in which membrane components linked to actin couple the treadmilling cytoskeleton to the surrounding fluid, thereby propelling the cell forward.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…In general, migration of mammalian cells without flagellum in suspension culture, completely in the absence of adhesion to a surface, has not been sufficiently studied so far. Aoun et al have recently described the primary lymphocyte mechanism of “swimming”, which is mainly due to rearward and inhomogeneous treadmilling of the cell external membrane, leading to a ‘‘paddling’’ of transmembrane proteins linked to and advected by the cell cortex [ 22 ]. Whether other cell types such as fibroblasts can “swim” is still a question; however, if this mode of motility is relevant, actin network contractility or actin polymerisation seems to play major roles under Rho family GTPases [ 23 ].…”
Section: Discussionmentioning
confidence: 99%